Mechanism of Tripterygium wilfordii Hook.F.- Trichosanthes kirilowii Maxim decoction in treatment of diabetic kidney disease based on network pharmacology and molecular docking - Lu, Lingfei; Peng, Jinting; Wan, Peijun; Peng, Hongcheng; Lu, Jiandong; Xiong, Guoliang (Frontiers in Pharmacology, 2022)
Background: Diabetic kidney disease (DKD) is the most common cause of end-stage renal disease. The effective treatment of DKD would rely on the incorporation of a multi-disciplinary. Studies have shown that Tripterygium wilfordii Hook.F. and Trichosanthes kirilowii Maxim have remarkable curative effects in treating DKD, but their combination mechanism has not been fully elucidated. Methods: We explored the mechanism of Tripterygium wilfordii Hook.F.-Trichosanthes kirilowii Maxim decoction (Leigongteng-Tianhuafen Decoction,LTD) in the treatment of DKD by network pharmacology and molecular docking. The main active components and action targets of LTD were collected from Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) database. The speculative targets of DKD were obtained from GeneCards, DisGeNET, and Online Mendelian Inheritance in Man (OMIM) databases. Then, an herb-component-target network was constructed based on the above analyses. The biological function of targets was subsequently investigated, and a protein-protein interaction (PPI) network was constructed to identify hub targets of DKD. The gene ontology (GO) function enrichment analysis and kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis were performed by RStudio. Finally, molecular docking was performed by AutoDock Vina and PyMOL software to explore the interaction between compounds and targets. Furthermore, the DKD model of human renal tubular cells (HK-2) induced by high glucose (HG) was selected, and the predicted results were verified by western blot analysis and immunofluorescence. Results: A total of 31 active components of LTD were screened out, and 196 targets were identified based on the TCMSP database. A total of 3,481 DKD related targets were obtained based on GeneCards, DisGeNET, and OMIM databases. GO function enrichment analysis included 2,143, 50, and 167 GO terms for biological processes (BPs), cellular composition (CCs), and molecular functions (MFs), respectively. The top 10 enrichment items of BP annotations included response to lipopolysaccharide, response to molecule of bacterial origin, response to extracellular stimulus, etc. CC was mainly enriched in membrane raft, membrane microdomain, plasma membrane raft, etc. The MF of LTD analysis on DKD was predominately involved in nuclear receptor activity, ligand-activated transcription factor activity, RNA polymerase II-specific DNA-binding transcription factor binding, etc. The involvement signaling pathway of LTD in the treatment of DKD included AGE-RAGE signaling pathway in diabetic complications, IL-17 signaling pathway, insulin resistance, TNF signaling pathway, etc. Molecular docking results showed that kaempferol, triptolide, nobiletin, and schottenol had a strong binding ability to PTGS2 and RELA. Furthermore, the in vitro experiments confirmed that LTD effectively decreased the expression of PTGS2, NF-κB, JNK, and AKT in the HG-induced DKD model. Conclusion: The findings of this study revealed that the therapeutic efficacy of LTD on DKD might be achieved by decreasing the expression of PTGS2, NF-κB, JNK, and AKT, which might improve insulin resistance, inflammation, and oxidative stress. These findings can provide ideas and supply potential therapeutic targets for DKD.